2013
DOI: 10.6063/motricidade.9(4).96
|View full text |Cite
|
Sign up to set email alerts
|

Relações entre o compromisso desportivo e o comportamento de consumo de desporto

Abstract: The purpose of this study was to examine the relationships between sport commitment and three types of sport consumer behaviors: participation frequency, sporting goods and media consumption. A survey was conducted among sport participants of both individual and team sports, fitness and outdoor activities (n= 900). The survey included questions related to demographic information, measures of sport commitment and sport consumption behavior. The results analyzed trough structural equation modeling showed that th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…Fernandes defines purchasing behaviour as when consumers make a purchase decision for sportrelated products or services (e.g., tickets, membership, sport-wears) that satisfy the demand of the consumer [4]. From a spectator's perspective, they would not make a purchasing decision unless the result of their searching, engaging, or assessing behaviour satisfies their demand.…”
Section: Sport Market Structuresmentioning
confidence: 99%
See 1 more Smart Citation
“…Fernandes defines purchasing behaviour as when consumers make a purchase decision for sportrelated products or services (e.g., tickets, membership, sport-wears) that satisfy the demand of the consumer [4]. From a spectator's perspective, they would not make a purchasing decision unless the result of their searching, engaging, or assessing behaviour satisfies their demand.…”
Section: Sport Market Structuresmentioning
confidence: 99%
“…Studies have found a relationship between participants' involvement and purchasing intention. Using social exchange theory, Fernandes et al (2013) empirically studied consumer behaviour and sports involvement [4]. Their results indicated consumers' purchase intention is directly proportional to the amount of time they devote to sports.…”
Section: Consumer Involvementmentioning
confidence: 99%
“…Sports consumption behavior can be defined as a set of activities performed when exploring for, participating in, and evaluating the sports activities that consumers believe will satisfy their needs (3) . Sports have been played and consumed in many different ways by different demographics of society.…”
Section: Introductionmentioning
confidence: 99%
“…The major difference that lies between recreational and professional sports is that when someone undertakes any sport for just recreational purposes, they engage with the sport sporadically unlike professional sports where the sport or physical activity is performed consistently for a longer duration. The magnitude of participation in sports is different also because of the access to different types of sporting accessories (3) . Some sections of the society play some or the other form of sports just for recreational and fun purposes, the others play to compete and represent some sort of level (state, national) where they can get recognition for themselves while the others engage with sports solely to sustain an active lifestyle and keep illnesses at bay.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation